Did EU regional spending affect the Brexit referendum?. Issue 1 (1st January 2018) - Huggins, Christopher
ABSTRACT: This paper explores whether European Union (EU) regional spending influenced how local areas voted in the UK's 2016 EU referendum. While much focus has been on identity and demographic factors in explaining the referendum result, little attention has been paid to the role of EU interventions in the UK's regions. This paper provides an initial exploration into this by assessing the role of EU regional spending. It finds the level of EU spending in local areas had little impact on how those areas voted in the referendum, raising questions about the communication and awareness of EU regional spending.